The methodology of modeling of electronic properties of bulk semiconductor compounds - A. V. Krivosheeva; V. L. Shaposhnikov; V. E. Borisenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An analysis of modern methods of modeling of the fundamental electronic properties of bulk semiconductors based on the electron density functional theory is performed and a technique taking into account the peculiarities of semiconductor compounds has been proposed. The procedure of creation of a model of the investigated object and an estimation of its adequacy is described. As an example the comparison of the results of calculations of electronic spectra and optical functions of MoS2 obtained in the framework of various functionals is given. The parameters which adequately describe the properties of investigated material in the framework of the presented technique are established.